Zero-Tolerance Policies: Do They Inhibit or Stimulate Illicit Drug Consumption? - Caulkins, Jonathan P. (Management Science, 1993)
Some have suggested fighting the drug problem with so-called “zero-tolerance” policies that impose stiff sanctions for possession of even trace amounts of illicit drugs. Such policies can swamp the criminal justice system and violate the principle that the punishment should fit the crime, but these objections have often been suppressed by an overriding desire to minimize consumption. This paper argues to the contrary that under plausible conditions zero-tolerance policies may actually encourage controlled users to consume more, not less, than they would if the punishment increased in proportion to the quantity possessed at the time of arrest. This result holds even if for every quantity the punishment under the proportional policy is less than or equal to that under the zero-tolerance policy. The argument relies on a mathematical model that describes how a typical controlled user's purchasing habits are affected by the punishment anticipated as a function of the quantity possessed. A variety of possible punishment policies are evaluated. The consumption minimizing policy for a given individual user is obtained, as well as the consumption minimizing policy that belongs to a restricted class of policies that are more likely to be politically feasible.